PENGARUH TIME BUDGET PRESSURE,LOCUS OF CONTROL, KOMITMEN ORGANISASI, DAN STRES KERJA TERHADAP KUALITAS AUDIT DENGAN PERILAKU DISFUNGSIONAL AUDIT SEBAGAI VARIABEL INTERVENING (Studi Empris pada Kantor Akuntan Publik Pekanbaru, Padang dan Medan) - Kristanti, Margaretha Sonya; Anugerah, Rita; Hasan, Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research is aimed to examine and find out evidence of the influence of time budget pressure, locus of control, organizational commitment, and job stress on audit quality. It also attemps to examine wheter dysfunctional audit behavior as mediatevariable.Data for this study were collected by using 99 questionnaires, which were distributed to auditors working at Public Accountants Firms. The sampling technique used is non-probability sampling using purposive sampling method. In total 60 questionnaires received were complete and hence usable in analysis. Data analysis method to examine each of the variabels and testing hypothesis were done through reliability test, validity test, normality test, the classical assumption test, test the coefficient determination, and T-test using multiple linear regression that is path analysis with SPSS 20.0.The result of this study indicates that the times budget pressurehave effects on audit quality with significant 0,022,locus of controlhave effects on audit quality with significant 0,006, organizational commitmenthave effects on audit quality with significant 0,031, job stresshave effects on audit quality with significant 0,031,time budget pressure indirectly effects on audit quality through dysfunctional audit behavior with significant 0,000, but locus of control, organizational commitment, and job stress did not indirectly effects on audit quality through dysfunctional audit behavior.Keywords : Time Budget, Control, Organizational, Stress, Behavior, And Audit Quality.